Numerical Prediction of Differences in Micromechanical Fracture Sequence in Notched and Un-Notched Wires for Civil Engineering Applications - Adewole, K.K.; Bull, S.J. (Institute of Research and Community Outreach - Petra Christian University, 2014)
The need to employ simulation-based investigations of fracture of civil engineering structures has been emphasised recently in literature. In this paper, three dimensional finite element simulations revealed that the cup and cone fracture process in channel-shaped notched wire for civil engineering applications begins with a slant fracture at the root of the outer edge of the channel-shaped notch and follows a slant to flat fracture sequence. These results demonstrate that the fracture origin in cup and cone fracture in notched wires for civil engineering applications does not necessarily begin with a flat fracture at the center of the wire and does not necessarily follows the flat to slant fracture sequence or propagation generally reported in literature. These results further demonstrate the need to employ simulation-based methodologies in conjunction with or as an alternative to purely experimental fractographic analysis for an accurate failure analysis of wires used for civil engineering applications.